Meta Analysis: Enhancing Mathematical Representation Ability Through The Discovery Learning - Mardani, Maya; Nurhanurawati, Nurhanurawati; Rosidin, Undang (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
To date, numerous studies have explored mathematical representation abilities delivered through the Discovery Learning. This study aims to identify and analyze published research on the effectiveness of the Discovery Learning in enhancing students' mathematical representation abilities using a meta analysis. The data analyzed consists of 10 articles published in online journals. The Discovery Learning as the independent variable and mathematical representation ability as the dependent variable. Based on the calculation results, the average effect size was 3,08 categorized as very large, and the paired sample t-test showed a significant difference in students' mathematical representation abilities before and after being taught using the Discovery Learning. From these results, it can be concluded that the Discovery Learning significantly enhances mathematical representation abilities.